Ćwiczenie tłumaczeniowe w dydaktyce przekładu jako element diagnozy początkowej - Aleksander Gomola (Ksiegarnia Akademicka Publishing, 2017)
Translation Exercise in Translation Didactics as a Component of Needs Analysis The article analyzes the results of a translation exercise used as an element of needs analysis to assess translation competences (as defined by EMT programme) of 30 M.A. translation trainees commencing an English-Polish translation course. It analyzes translation samples of selected sentences from a travelogue narrative, with specific translation problems (collocations, passive voice structures, a cleft sentence with a passive gerund) in terms of translation mistakes as defined by Hejwowski. An analysis of the samples shows that a translation exercise, if properly selected, allows to identify translation trainees’ translation competences and translation mistakes, and may be helpful in designing a translation course and as an element of action research approach applied during the course.